Development of Electronic Module Based Microalgae and Testing Water Quality in Environmental Change Material to Improve Environmental Attitudes for High School Students - Murti, Andi Basliawanti; Sueb, Sueb; Muhdar, Mimien Henie Irawati Al (BIOEDUKASI, 2024)
One of the global problems that often occurs in society is environmental pollution, one of which is water pollution. The impact of water pollution is in the form of ecosystem damage and decreased water quality. One of nature's efforts to prevent environmental pollution in waters is by having bioindicators in waters, one of which is microalgae. However, if the community is less sensitive to environmental sustainability, environmental pollution will continue to occur. Therefore, public awareness is needed to protect the environment, one way is to foster an attitude of environmental concern among high school students by creating teaching materials related to the environment. To make it easier for students to understand and use the teaching materials, teaching materials were made in the form of PBL-based electronic modules that integrate materials related to microalgae and water quality to improve the environmental concern of class X high school students in a valid, practical and effective manner. The subjects used in this study were four classes of class X students of SMAN 12 Makassar. The instrument used in this study was an environmental concern attitude questionnaire that had been validated by experts. The results of this study can be categorized as valid, practical and effective because the validity results obtained 100% from the material expert validator, 92.2% from media and teaching materials experts, and 89.3 from biology education practitioners. While for the practicality test, there are 3 categories, namely, for individual tests the results were 86.58%, small group tests of 87.42%, and field tests of 87.44%. The effectiveness test is divided into 5 tests, namely, normality test, homogeneity test, N gain test, T test and ANCOVA test, where all tests obtained the results of the electronic module effectively used as teaching materials for class X of high school. This shows that the electronic module has an influence on the environmental care attitude of high school students in class X.